Implementasi Manajemen Personalia Pendidikan Islam Berbasis Pengabdian di Pondok Pesantren Wali Songo Ngabar, Jawa Timur - Fery Diantoro (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2020)
Dedicated personnel in pesantren have a great responsibility towards the management of education, even though the quality and qualifications are not the same as education personnel in general. Pondok Pesantren Wali Songo Ngabar presents and provides programs to improve their quality through the personnel management approach. This research is a descriptive study with a qualitative approach. Data were collected through interviews, observation, and documentation. The results of the discussion showed that the dedicated personnel at Pondok Pesantren Wali Songo Ngabar were an integrated unit of educational human resources that functioned as educators. Devotion as an embodiment to explore and practice the teachings of Islam (tafaqquh fi al-din), train to be human beings, and strengthen expertise to engage and serve in the community. Management is applied based on morality and Islamic values that prioritize local wisdom, culture, and independence of Pesantren in an effort to create the professional staff.